On the Difference Equation 𝑥𝑛+1=𝑥𝑛𝑥𝑛−2−1 - Candace M. Kent; Witold Kosmala; Stevo Stević (Abstract and Applied Analysis)
The long-term behavior of solutions of the following difference equation: 𝑥𝑛+1=𝑥𝑛𝑥𝑛−2−1, 𝑛∈ℕ0, where the initial values 𝑥−2, 𝑥−1, 𝑥0 are real numbers, is investigated in the paper.